EP518 'Sandwich' adjuvant chemotherapy and radiotherapy in high risk endometrial cancer: two institution experience. (1st November 2019) - Ferrero, A; Danese, R; Fuso, L; Danese, S; Gribaudo, S; Rossi, A; Attianese, D; Villa, M; Biglia, N
Abstract : Introduction/Background: High-risk endometrial cancer represents a heterogeneous group of patients with an increased risk of pelvic and distant recurrences and worse outcome. The standard adjuvant treatment has not been established; controversy exists regarding the combination of chemotherapy (CT) and radiotherapy (RT) and their optimal timing. The 'sandwich' approach involves adjuvant CT followed by RT and subsequent CT; previous studies investigated different treatment modalities in a limited number of patients. Aim of this study is to assess efficacy and tolerability of a standardized 'sandwich' approach in high risk endometrial cancer. Methodology: A retrospective study was conducted in two Gynaecological Oncology Units (Mauriziano and Sant'Anna Hospitals) in Torino, Italy, from 01/01/2003 until 31/12/2016. High risk patients according to histological type, FIGO stage, grade and lymphovascular invasion, with available clinical data were included. The 'sandwich' method consisted of three cycles of platinum based CT, followed by (external and brachy) RT and than three cycles of platinum based CT. Compliance to treatment, CT and RT toxicities, Disease Free Survival (DFS), Cancer Specific Survival (CSS) and Overall Survival (OS) were analyzed. Results: 98 patients (median age 65 years, 36–77) were selected: 55 hystological type1 and 43 type 2; 27 FIGO I–II stages and 71 III–IV. Most of the patients (70.4%) received a Carboplatin-Paclitaxel combination. 558 (94.9%) CT cycles were completed and only 3 required a dose reduction. Grade 2 and 3 hematological toxicity rates were 3.1 and 4.1%. Grade 2 gastrointestinal and grade 2 genitourinary toxicity were reported in 8.2% and 2% of cases. With a median follow-up of 52 months, DFS was 77.6%, CSS 82.7% and OS 69.4%. Conclusion: In our experience 'sandwich' chemotherapy and radiotherapy combination is an effective adjuvant treatment with a low toxicity in high risk endometrial cancer. Disclosure: Nothing to disclose.